2016
DOI: 10.1074/jbc.m116.729194
|View full text |Cite
|
Sign up to set email alerts
|

Direct Binding to Replication Protein A (RPA)-coated Single-stranded DNA Allows Recruitment of the ATR Activator TopBP1 to Sites of DNA Damage

Abstract: A critical event for the ability of cells to tolerate DNA damage and replication stress is activation of the ATR kinase. ATR activation is dependent on the BRCT (BRCA1 C terminus) repeatcontaining protein TopBP1. Previous work has shown that recruitment of TopBP1 to sites of DNA damage and stalled replication forks is necessary for downstream events in ATR activation; however, the mechanism for this recruitment was not known. Here, we use protein binding assays and functional studies in Xenopus egg extracts to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…While MDC1 recognition involves the same surface on BRCT5, the MDC1 peptide binds in an opposite orientation to that observed for BLM, and is of lower affinity and specificity, relying primarily on electrostatic interactions between the highly negatively charged MDC1 phosphopeptide and the positively charged surface of BRCT5. Our results raise further doubts as to whether MDC1 is a physiological binding partner for BRCT5 of TopBP1 (Blackford et al, 2015; Choi and Yoo, 2016), although a similar electrostatic interaction may also explain reports of interactions between BRCT5 and single stranded DNA, which have been suggested to play a role in the recognition of stalled DNA replication forks (Acevedo et al, 2016). …”
Section: Discussionsupporting
confidence: 49%
“…While MDC1 recognition involves the same surface on BRCT5, the MDC1 peptide binds in an opposite orientation to that observed for BLM, and is of lower affinity and specificity, relying primarily on electrostatic interactions between the highly negatively charged MDC1 phosphopeptide and the positively charged surface of BRCT5. Our results raise further doubts as to whether MDC1 is a physiological binding partner for BRCT5 of TopBP1 (Blackford et al, 2015; Choi and Yoo, 2016), although a similar electrostatic interaction may also explain reports of interactions between BRCT5 and single stranded DNA, which have been suggested to play a role in the recognition of stalled DNA replication forks (Acevedo et al, 2016). …”
Section: Discussionsupporting
confidence: 49%
“…In UV-irradiated cells, the signal that triggers the activation the ATR-CHK1 pathway is thought to be regions of single-stranded DNA (ssDNA) produced by replicative helicase-polymerase uncoupling (15) and by gaps generated during nucleotide excision repair (16 -18). This ssDNA is thought to then become bound by replication protein A (RPA), which coordinates many aspects of ATR-CHK1 signaling (19 -21), including the recruitment of the ATR kinase (22), its activator module comprised of the 9-1-1 clamp and TopBP1 (23)(24)(25)(26), and the adaptor proteins Timeless, Tipin, and Claspin, which specifically facilitate the phosphorylation of CHK1 (27). The importance of the ATR-CHK1 pathway in DNA damage responses and carcinogenesis is highlighted by mouse genetic studies in which loss of one allele of either ATR or CHK1 has been shown to promote tumorigenesis (28 -31), including in the skin (32).…”
mentioning
confidence: 99%
“…Current models assume that the strand serving as leading template enters a central channel in Mcm2‐7 thus melting the parental DNA duplex to generate two downstream single stranded filaments . Replication Protein A complex (RPA), constituted by three (Rfa1, Rfa2, and Rfa3) subunits, binds and stabilizes ssDNA to facilitate DNA synthesis and perform key functions in response to replication stress . DNA polymerase ϵ (Pol ϵ), composed of four polypeptides (Pol2, Dpb2, Dpb3, and Dpb4), tightly associates to the CMG helicase through the GINS and Cdc45 components .…”
Section: Architecture and Function Of The Eukaryotic Replisomementioning
confidence: 99%
“…[43,44] Replication Protein A complex (RPA), constituted by three (Rfa1, Rfa2, and Rfa3) subunits, binds and stabilizes ssDNA to facilitate DNA synthesis and perform key functions in response to replication stress. [45][46][47] DNA polymerase e (Pol e), composed of four polypeptides (Pol2, Dpb2, Dpb3, and Dpb4), tightly associates to the CMG helicase through the GINS and Cdc45 components. [48] The largest subunit Pol2 bears both DNA polymerase and 3 0 -5 0 exonuclease activities and is arranged in two large domains that likely raised via duplication of a single ancestral protein.…”
Section: Leading and Lagging Strand Polymerases Associate To A Helicamentioning
confidence: 99%